2018
DOI: 10.1242/jeb.165860
|View full text |Cite
|
Sign up to set email alerts
|

Multiple spectral channels in branchiopods. I. Vision in dim light and neural correlates

Abstract: Animals that have true color vision possess several spectral classes of photoreceptors. Pancrustaceans (Hexapoda+Crustacea) that integrate spectral information about their reconstructed visual world do so from photoreceptor terminals supplying their second optic neuropils, with subsequent participation of the third (lobula) and deeper centers (optic foci). Here, we describe experiments and correlative neural arrangements underlying convergent visual pathways in two species of branchiopod crustaceans that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…We have found that ephemeral pool habitats, at less than 1 m of depth, are often dimmer than terrestrial habitats under starlight. In a companion article (Lessios et al, 2018), we found that branchiopod apposition compound eyes are likely to generate reliable signals at such intensities. There is some neuroanatomical evidence that pancrustaceans might incorporate summation from compound eye ommatidia in the lamina of their optic lobes for reliable vision at low intensities (Glantz, 2014;O'Carroll and Warrant, 2017;Warrant, 2017).…”
Section: Multiple Spectral Classes Predominantly For Luminancedriven mentioning
confidence: 81%
See 4 more Smart Citations
“…We have found that ephemeral pool habitats, at less than 1 m of depth, are often dimmer than terrestrial habitats under starlight. In a companion article (Lessios et al, 2018), we found that branchiopod apposition compound eyes are likely to generate reliable signals at such intensities. There is some neuroanatomical evidence that pancrustaceans might incorporate summation from compound eye ommatidia in the lamina of their optic lobes for reliable vision at low intensities (Glantz, 2014;O'Carroll and Warrant, 2017;Warrant, 2017).…”
Section: Multiple Spectral Classes Predominantly For Luminancedriven mentioning
confidence: 81%
“…There is also evidence that recently duplicated paralogs are maintained at a much higher rate than would be expected given homogenization by gene conversion (Colbourne et al, 2011). In a companion paper (Lessios et al, 2018), we suggest that branchiopods have maintained four spectral classes of photoreceptors in their compound eyes, which is supported by the number of opsins expressed in anostracan and notostracan compound eyes (Kashiyama et al, 2009). Based on the number of spectral photoreceptor classes alone, it might be assumed that these species possess tetrachromatic vision.…”
Section: Light Attenuation and Behavioral Depth Regulation In Temporamentioning
confidence: 84%
See 3 more Smart Citations